Loss of ALBINO3b Insertase Results in Truncated Light-Harvesting Antenna in Diatoms . Issue 3 (29th August 2019) - Nymark, Marianne; Volpe, Charlotte; Hafskjold, Marthe Caroline Grønbech; Kirst, Henning; Serif, Manuel; Vadstein, Olav; Bones, Atle Magnar; Melis, Anastasios; Winge, Per
Abstract : Diatom ALB3b is required for insertion of Fx-Chl-binding proteins in thylakoid membranes and has a novel conserved domain implying that its interaction partners differ from those in plants/green algae. Abstract: The family of chloroplast ALBINO3 (ALB3) proteins function in the insertion and assembly of thylakoid membrane protein complexes. Loss of ALB3b in the marine diatom Phaeodactylum tricornutum leads to a striking change of cell color from the normal brown to green. A 75% decrease of the main fucoxanthin-chlorophyll a/c -binding proteins was identified in the alb3b strains as the cause of changes in the spectral properties of the mutant cells. The alb3b lines exhibit a truncated light-harvesting antenna phenotype with reduced amounts of light-harvesting pigments and require a higher light intensity for saturation of photosynthesis. Accumulation of photoprotective pigments and light-harvesting complex stress-related proteins was not negatively affected in the mutant strains, but still the capacity for nonphotochemical quenching was lower compared with the wild type. In plants and green algae, ALB3 proteins interact with members of the chloroplast signal recognition particle pathway through a Lys-rich C-terminal domain. A novel conserved C-terminal domain was identified in diatoms and other stramenopiles, questioning if ALB3b proteins have the same interaction partners as their plant/green algae homologs.